2006
DOI: 10.1007/s00253-006-0391-9
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic production of enantiopure cyclohexane-trans-1,2-diol using extracellular lipases from Bacillus subtilis

Abstract: Two extracellular lipases from Bacillus subtilis, B. subtilis lipase A and lipase B, have been expressed in the heterologous host Escherichia coli, biochemically characterized and used for the kinetic resolution of (rac)-trans-1,2-diacetoxycyclohexane. Both enzymes were selectively acting on the (R,R)-enantiomer of the racemic substrate, highly specifically hydrolyzing only one of the two ester groups present, thus allowing the preparation of enantiopure (R,R)- and (S,S)-cyclohexane-trans-1,2-diol. The reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Product analysis revealed that only one diastereomer with anti 1,2-diacetoxy groups was prepared by the reaction of cyclohexene oxide with acetic anhydride, which gives exclusively the corresponding trans-1,2-diacetate. Stereochemical assignment was achieved by: i) comparison of the obtained 1 H NMR spectrum with one of authentic sample reported in the literature, 16 and ii) hydrolysis of rac-trans-1,2-diacetoxycyclohexane to white crystalline rac- …”
Section: Resultsmentioning
confidence: 99%
“…Product analysis revealed that only one diastereomer with anti 1,2-diacetoxy groups was prepared by the reaction of cyclohexene oxide with acetic anhydride, which gives exclusively the corresponding trans-1,2-diacetate. Stereochemical assignment was achieved by: i) comparison of the obtained 1 H NMR spectrum with one of authentic sample reported in the literature, 16 and ii) hydrolysis of rac-trans-1,2-diacetoxycyclohexane to white crystalline rac- …”
Section: Resultsmentioning
confidence: 99%
“…Lyophilized BSA was purchased from Sigma-Aldrich (Taufkirchen, Germany). Lipases A and B from B. subtilis (BSL-A and BSL-B) were produced and purified as described previously [53]. Briefly, for large-scale production of BSL-A and BSL-B, high cell density fed-batch cultivation using E. coli BL21(DE3) as a host, carrying pET19b derived expression plasmids were performed in an Infors fermenter (30 L) [53-55].…”
Section: Methodsmentioning
confidence: 99%
“…Lipases A and B from B. subtilis (BSL-A and BSL-B) were produced and purified as described previously [53]. Briefly, for large-scale production of BSL-A and BSL-B, high cell density fed-batch cultivation using E. coli BL21(DE3) as a host, carrying pET19b derived expression plasmids were performed in an Infors fermenter (30 L) [53-55]. After purification by immobilized-metal affinity chromatography (IMAC) [56] using a Ni-nitrilo-triacetic acid (NTA) superflow column (30 mL, QIAGEN, Hilden, Germany), imidazole was removed by gel filtration chromatography (G-25 column, Amersham Pharmacia Biotech) using glycine/NaOH-buffer (10 mM, pH 10).…”
Section: Methodsmentioning
confidence: 99%
“…Lipase A from Bacillus subtilis is a well‐characterised enzyme. It is one of the smallest lipases known, with a size of 19 kDa, and shows good hydrolytic activity in medium‐length substrates (Dartois et al ., ; Lesuisse et al ., ), having been used for the production of fine chemicals (Detry et al ., ). Its crystal structure is known (Van Pouderoyen et al ., ), making it possible to elucidate the structural basis of its stability at different pH (Rajakumara et al ., ), and site saturation mutagenesis has been used to study the role of specific amino acids in the properties of the enzyme (Fulton et al ., ).…”
Section: Introductionmentioning
confidence: 97%